Specific Short Tandem Repeat Loci Detection in Prenatal Diagnosis of Fetal Chromosomal Diseases: Specific STR Loci in Fetal Chromosomal Diseases - Cao, Xian; Liu, Jiangyue; Ling, Mengsi; Chen, Hongjing; Mao, Yifan; Cui, Aimin; Jiang, Hongru (Cellular and Molecular Biology, 2023)
It was to investigate the value of quantitative fluorescence PCR (QF-PCR) for the selection of specific short tandem repeat (STR) in prenatal diagnosis of fetal chromosomal diseases. Amniotic fluid (AF) and villus samples were obtained from 80 pregnant women at 16-20 weeks of gestation, and venous blood samples were obtained from 60 normal individuals to extract and prepare peripheral blood chromosome, AF cell chromosome, and villus cell chromosome samples for specific STR locus detection. It showed that the area ratio of AMX peak to AMY peak in the Genescan typing map of peripheral blood DNA of normal males was close to 1:1, while the Genescan typing map of peripheral blood DNA of normal females had only AMX peak and no AMY peak. Normal heterozygous individuals had an area ratio between 1 and 1.45 for venous blood, 1.002 and 1.27 for villous samples, and 1 and 1.35 for AF samples. The karyotype of a male fetus was 46, XY, inv [9] (p11: q13), and the structure of fetal chromosome 9 was inverted (interarm), and the site of structural inversion was band 1 in the short breech 1 region and band 3 in the long arm 1 region of chromosome 9. It suggested that QF-PCR can effectively identify the normal human body and cases by selecting specific STR locus detection, which has a good application value for prenatal diagnosis of fetal chromosomal diseases.